The Efficacy of Magic Card Games on Eaely Hijaiyah Letter Childhood Recognition - Ramadani, Wulan; Nurhayati, Nurhayati; Amrullah, Amrullah; Agusniatih, Andi (FKIP - Universitas Riau, 2025)
This study discusses the problem of inadequate development in recognizing Hijaiyah letters. The purpose of this study is to find out the effectiveness of magic card games for young children in recognizing Hijaiyah letters. The research method used is quantitative, in particular, experimental studies. The subjects consisted of 13 children, 7 boys and 6 gils, from Group B1 of the Samporoa Pembina State Kindergarten. Data collection techniques include observation, documentation, and interviews. Based on the recapitulation of the initial and final observations regarding the ability to recognize the last Hijaiyah before and after the intervention, the category of